Efficacy, safety, and biomarker analysis of TACE combined with lenvatinib plus sintilimab in unresectable hepatocellular carcinoma: a real-world study - Lingzhan Meng; Hu Li; Yingjie Ji; Peng Yu; Zizheng Wang; Li Cao; Bin Shi; Yanling Shao; Jin Yan; Yinjie Gao; Zhenyu Zhu (Cancer Immunology, Immunotherapy)
Abstract Background The integration of transarterial chemoembolization (TACE) with systemic therapy has demonstrated improved survival outcomes in patients with unresectable hepatocellular carcinoma (HCC). However, there is limited evidence evaluating the combination of TACE with the systemic regimen of anti-PD-1/L1 inhibitor plus lenvatinib. This study aims to assess the efficacy and safety of TACE combined with lenvatinib and sintilimab in unresectable HCC patients. Methods Unresectable HCC patients who received TACE in combination with sintilimab plus Lenvatinib as first-line treatment from 1 January 2020 to 31 March 2023 were included for the analysis. Overall survival (OS), progression-free survival (PFS), objective response rate (ORR) and disease control rate (DCR) were evaluated by modified Response Evaluation Criteria in Solid Tumors criteria. Exploratory biomarker analysis was conducted. Results The study included 70 patients with unresectable HCC, predominantly male and infected with Hepatitis B. The median follow-up duration for the whole cohort was 13.8 months (95% CI 11.08–16.7). The ORR was 61.4% (95% CI, 49.0%–72.8%) and the DCR was 68.6% (95%CI, 56.4%–79.2%). The median PFS was 13.2 months (95% CI 11.0-NA), with a corresponding 1-year PFS rate of 50.3% (95% CI 39.7%-65.5%). The median OS was not reached, and the 1-year OS rate was 89.3% (95% CI 81.4%–97.9%). The most common treatment-related adverse events (TRAEs) were fatigue 38.6% (27/70), hypertension 32.9% (23/70), and hand-foot syndrome 31.4% (22/70). Most TRAEs were mild-to-moderate and manageable. In addition, significant predictive value was found in alpha-fetoprotein levels (AFP), with patients showing a level of decrease post-treatment having better PFS. Conclusion The combination regimen demonstrated promising efficacy in treating unresectable HCC, accompanied by manageable safety profiles. Furthermore, the results of this investigation suggest that AFP holds promise as predictive biomarkers for this treatment strategy.